Importância da avaliação da hemoglobina fetal na clínica da anemia falciforme - RIBEIRO, Rita de Cassia Mousinho (2013)
Sickle cell disease is one of the commonest and most studied genetic diseases in the world. Caused by a mutation of the β gene, it changes the molecular structure of hemoglobin. Abnormal Hb S molecules suffer polymerization physiologically provoked by a low oxygen tension, acidosis and dehydration. As a result, red blood cells take on a sickle cell form, which causes microvascular occlusion with varying consequences. The objective of this study was to review the importance of fetal hemoglobin in the clinical assessment of sickle cell disease patients. It has been shown that the association of high levels of fetal hemoglobin with sickle cell disease is favorable in hematological terms. In this interaction, F cells have low Hb S concentrations and thus inhibit Hb S polymerization and the morphological alteration of red blood cells. Treatment with hydroxyurea resulting in an increased fetal hemoglobin expression brings about a significant improvement in the patient's clinical state. Thus, fetal hemoglobin constitutes the greatest inhibitor of desoxi-Hb S polymerization and avoids the morphological alteration of red blood cells, chronic hemolytic anemia, painful microvascular occlusive crises, bone infarction and necrosis of several organs thereby improving the clinical outcome and the patients' life expectancy.